Effectiveness of almond gum trees exudate as a novel edible Coating for improving postharvest quality Of cucumber (cucumissativus l.) - R. DHANUSHA; K.A. ATHMASELVI (International Journal of Pharma and Bio Sciences, 2018)
The food safety and quality has been given more significance in the sustenance in food research field. The attractiveness of the food mostly relies on appearance, enhance, shading, surface, wholesome esteem and microbial security. These can be kept up by utilizing reasonable biodegradable packaging, for example, palatable films and coatings. These have similar effects of modified atmospheric packaging which alters the atmosphere surroundings of food products. These films and coatings can be produced from polysaccharides, proteins, and lipids. In this study, the application of almond gum based edible coating on quality and shelf life of cucumber (CucumissativusL.) vegetables during storage at ambient condition was investigated. Formulations consist of almond gum, potassium Sorbate, Ajowan oil, glycerol, water and Tween 80. Different quality parameters were monitored to evaluate the coating effects. The parameters included weight loss, Total soluble solids, pH, colour, titratable acidity, total phenolic, water activity and sensory analysis. The coating improved the quality of post harvest vegetable in terms of weight loss, acidity, total phenolic content water activity and thereby increased the postharvest self-life of cucumbers at ambient conditions.